FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KONTRASEPSIMETODE OPERATIF WANITA (MOW) - Lestari, Heni (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
The number of couples in fertility age in RejangLebong is about 56.345. In RejangLebong,the users of contraception type Woman Operative Method (MetodeOperatifWanita-MOW) have not reached the target yet. Here, the discrepancy in using the contraception aids stilloccurs. This research aims to know the factors related to the way in choosing the the contraceptiontype MOW. The design of this research is cross sectional method. The population is about5534 people and the sample is 67 people. The sample was chosen by using cluster sampling. Theresearch was done in Public Health Center or Puskesmas at Perumnas, RejangLebong. This researcherhas been done from March until April 2014. The instrument used of this research wasquestionnaire. The questionnaire was used to get the data. Then the data was analyzed based onthe analysis univariat and bivariat by applying the Chi-Square test. The result showed that 52,2%sample used contraception type MOW. There were correlation between parity (p=0,29), education(p=0,71), knowledge (p=0,17), and partner support (p=0,06), and the choice of contraceptiontype MOW. From the finding of the research, the couples in fertility age who have parity≥ 2or more than 35 years old are better to use the contraception typeMOW.